Measuring above-ground carbon stock using spatial analysis and the InVEST model: Application in the Thoria Watershed, India - Guo, Zhe; Sharma, Himani; Jadav, Mahesh; Hettiarachchi, Upeksha; Guha, Chiranjit; Zhang, Wei; Priyadarshini, Pratiti; Meinzen-Dick, Ruth S. (IOP Publishing, 2024)
Understanding and quantifying above-ground carbon stock is critical for assessing the impact of land use choices on carbon emissions which can inform conservation and management strategies to protect and increase carbon stocks. This study introduces a novel methodology for evaluating above-ground carbon storage and sequestration in the Thoria watershed, India, using time-series open-access remotely sensed datasets and the InVEST (Integrated Valuation of Environmental Services and Tradeoffs) carbon model. Our spatially explicit analysis examines land cover and land use changes over the past 20 years. Using high-resolution NDVI (Normalized Difference Vegetation Index) data from Sentinel satellites, we disaggregate land cover types into high and low NDVI classes, which allows enhanced assessment of carbon stocks by capturing the spatial variation within the same land cover types. To assess the potential impacts of land cover changes on carbon stock, we generated two future scenarios suggested by local experts: a 20% expansion of cropland and a 20% expansion of wooded land. Using a proximity-based approach, we create these future land use maps and estimate the corresponding carbon stock with the InVEST carbon model. We demonstrate the utility of the methodology in informing land use decisions through spatially explicitly assessing how carbon stock changes in response to cropland expansion and wooded land growth. Our findings indicate that while urban development contributes to carbon losses, increasing wooded land and tree cover helps mitigate these losses, highlighting the importance of afforestation in maintaining ecological balance and reducing environmental impact.